Does the Sensation-Seeking trait differ among participants engaged in sports with different levels of physical risk? - Gomà i Freixanet, Montserrat; Martha, Cécile; Muro, Anna (Anales de Psicología / Annals of Psychology, 2012)
This paper aims to establish to what extent participants engaged in different levels of physical risk sports differ in levels of Sensation Seeking (SS) trait. A systematic searching of the literature gave 36 peer-reviewed studies published until September 2010. Results suggested that high scores on Thrill and Adventure Seeking seem characteristic of participants engaged in sports with high and medium levels of risk, and to a lesser extent of low risk sports as well. High scores on Experience Seeking seem characteristic only of participants engaged in sports with high levels of risk. Scores on Boredom Susceptibility only differ when comparing participants engaged in high risk with those engaged in low risk sports. Finally, high scores on Disinhibition and high Total score seem characteristic of athletes at any level of risk as compared to controls, and of athletes engaged in high risk sports as compared to those engaged in low risk sports. We conclude that the SS scale is a useful tool to assess and interpret individual differences in personality that exist between sportspersons practicing sports with different levels of risk.